A Study and Assessment of Selected Elements of the Visual Aspects of Collectible Chocolate Packaging with the Use of the Eye - Tracking Method - Cholewa-WÃ³jcik, Agnieszka Sylwia; Åšwida, JarosÅ‚aw (Indian Journal of Marketing, 2015)
The visual aspect of packaging is a very important carrier of a specifically encoded market communication system. It is a certain form of a "language" that should lead to attracting the consumer's attention to a product, then decode the message, generate interest, trigger a purchase decision, and leave a long-lasting positive connotation. The aim of this study was to analyze the consumers' perception regarding the visual aspects of selected chocolate collectible wrappers with the use of the eye-tracking method. The subsidiary aim was to examine the reactions and acceptance of modern consumers to the visual aspects of the chocolate wrappers offered in the market in the 1970s and 1980s of the 20th century - a time when graphic designs were not directly connected with a product.